Information asymmetry leads to underpricing: validation through SEM for Indian IPOs. Issue 2 (4th July 2017) - Chhabra, Sheena; Kiran, Ravi; Sah, A.N.
Abstract : Purpose: The purpose of this paper is to examine the relevance of information, transparency and information efficiency in short-run performance of new issues. The current research evaluates the short-run performance of IPOs during 2005-2012, which even includes the recessionary period. The present study evaluates the impact of informational variables on first-day returns. Design/methodology/approach: The short-run performance of the IPOs is measured through market adjusted excess return. A structural equation model (SEM) has been designed to identify how information influences the short-run performance of IPOs. Findings: The results of structural model reveal that the sale of promoters' stake and underwriters' reputation are the major contributors towards information and are found to be highly significant statistically. The model also shows that the issue size (a component of information) is statistically insignificant at 5 per cent. The model suggests that the availability of information has negative impact on the first day returns indicating that the issuer which disclose maximum information to the public get lower returns on the listing day and hence, their issues are less underpriced. Originality/value: The present study has a contribution in investment decisions for global investors, as the participation of international investors is common in IPOs of emerging markets. The findings of the study are expected to be useful to the practitioners in predicting the pricing of IPOs based on the informational variables influencing their performance.